Simplified design of data converters - Lenk, John D. (EDN series for design engineers., 1997)
Simplified Design of Data Converters shows how to design and experiment with data converters, both analog-to-digital and digital to analog. The design approach here is the same one used in all of John Lenk's best-selling books on simplified and practical design. Throughout the book, design problems start with guidelines for selecting all components on a trial-value basis, assuming a specific design goal and set of conditions. Then, using the guideline values in experimental circuits, the desired results are produced by varying the experimental component values, if needed. If you are a w.